A STUDY ON OJAS AND OJAKSHAYA IN ETIOPATHOGENESIS OF MADHUMEHA (DIABETES MELLITUS) - Durgesh Senthiya; Meera K Bhojani; Mahesh Vyas; Pankaj Pathak (International Journal of Ayurveda and Pharma Research, 2020)
Ojas is considered as essence of seven Dhatus or equivalent to Bala or Sleshma. Ojas can also be considered as living radiant energy present in human body. In Ayurveda literature the term Oja is not clearly explained by Ayurveda community. The classical Ayurveda text describes Ojakshaya as one of the Ojavikara which may be prevalent in various diseases. The pathogenesis of Madhumeha (Diabetes Mellitus) also describes this phenomenon. The prevalence of Oja kshaya can be clinically evaluated in the patients of Madhumeha and the same if kept in mind during treatment may arrest the further progress of the disease to complications like Diabetic Retinopathy, Neuropathy etc. In Ayurveda classics Ojakshaya is described in relation of Madhumeha. So, there will be prevalence of Ojakshaya in patient of Madhumeha (Diabetes Mellitus). Therefore, in this review article an attempt is made to understand the concept of Oja and Ojakshaya in diabetes mellitus.